Does Prolonged Naltrexone Therapy Alter the Rewarding Nature of Exercise, Socialization, and Eating? A Narrative Review - Caitlin Collier; Thomas Hilton (McGill Journal of Medicine)
Introduction: Naltrexone is an opioid receptor antagonist prescribed for alcohol use disorder and opioid use disorder.  Naltrexone has a high affinity for the mu-opioid receptors, which are the primary binding site of beta-endorphin. Beta-endorphin is an endogenous opioid that functions as the mediator of behavioral reward and reinforcement. Antagonism of the mu-opioid receptors with naltrexone improves certain outcomes in patients with substance use disorder but may alter the positive endogenous reinforcement associated with naturally rewarding and healthy activities including exercising, socializing, and eating.